THE USE OF AUDIO-VISUAL AIDS IN EFL STUDENTS’ LISTENING COMPREHENSION OF IAII GENTENG, BANYUWANGI - Mufidah Yusroh (IKIP PGRI Pontianak, 2018)
This research is focused on analyzing the use of audio-visual aids in EFL students’ listening comprehension of IAI Ibrahimy Genteng Banyuwangi. This research is descriptive qualitative research that was set in three meetings. The subjects involved were the students of second semester. The data collection was accomplished by means of students' reflection on field notes of the observations, interviews and listening comprehension tests. The analysis was based on a constant comparison of data that were triangulated after being coded and categorized. The findings of this research were the students’ listening comprehension that was increased from the first listening test to the third listening test. Then, the record of the field notes and the interviews supported the findings from the listening comprehension tests. In another word, the use of audio-visual aids could increase the students’ listening comprehension and the students’ interest to learn English.Keywords: Audio-visual aids, students’ listening comprehension